Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Sure, let's break down the problem step-by-step and evaluate the given functions for [tex]\( x = -8 \)[/tex]:
1. Evaluate [tex]\( g(x) \)[/tex] at [tex]\( x = -8 \)[/tex]:
The function [tex]\( g(x) \)[/tex] is given by:
[tex]\[ g(x) = |x + 5| \][/tex]
Substitute [tex]\( x = -8 \)[/tex] into the function:
[tex]\[ g(-8) = |-8 + 5| = |-3| = 3 \][/tex]
So, [tex]\( g(-8) = 3 \)[/tex].
2. Evaluate [tex]\( h(x) \)[/tex] at [tex]\( x = -8 \)[/tex]:
The function [tex]\( h(x) \)[/tex] is given by:
[tex]\[ h(x) = \frac{1}{x + 7} \][/tex]
Substitute [tex]\( x = -8 \)[/tex] into the function:
[tex]\[ h(-8) = \frac{1}{-8 + 7} = \frac{1}{-1} = -1 \][/tex]
So, [tex]\( h(-8) = -1 \)[/tex].
3. Evaluate [tex]\( (g - h)(x) \)[/tex] at [tex]\( x = -8 \)[/tex]:
The expression [tex]\( (g - h)(x) \)[/tex] denotes the difference between [tex]\( g(x) \)[/tex] and [tex]\( h(x) \)[/tex]. Thus:
[tex]\[ (g - h)(x) = g(x) - h(x) \][/tex]
Substitute [tex]\( x = -8 \)[/tex]:
[tex]\[ (g - h)(-8) = g(-8) - h(-8) = 3 - (-1) = 3 + 1 = 4 \][/tex]
So, the value of [tex]\( (g - h)(-8) \)[/tex] is 4.
Therefore, the solution to the question is:
[tex]\[ (g-h)(-8) = 4 \][/tex]
1. Evaluate [tex]\( g(x) \)[/tex] at [tex]\( x = -8 \)[/tex]:
The function [tex]\( g(x) \)[/tex] is given by:
[tex]\[ g(x) = |x + 5| \][/tex]
Substitute [tex]\( x = -8 \)[/tex] into the function:
[tex]\[ g(-8) = |-8 + 5| = |-3| = 3 \][/tex]
So, [tex]\( g(-8) = 3 \)[/tex].
2. Evaluate [tex]\( h(x) \)[/tex] at [tex]\( x = -8 \)[/tex]:
The function [tex]\( h(x) \)[/tex] is given by:
[tex]\[ h(x) = \frac{1}{x + 7} \][/tex]
Substitute [tex]\( x = -8 \)[/tex] into the function:
[tex]\[ h(-8) = \frac{1}{-8 + 7} = \frac{1}{-1} = -1 \][/tex]
So, [tex]\( h(-8) = -1 \)[/tex].
3. Evaluate [tex]\( (g - h)(x) \)[/tex] at [tex]\( x = -8 \)[/tex]:
The expression [tex]\( (g - h)(x) \)[/tex] denotes the difference between [tex]\( g(x) \)[/tex] and [tex]\( h(x) \)[/tex]. Thus:
[tex]\[ (g - h)(x) = g(x) - h(x) \][/tex]
Substitute [tex]\( x = -8 \)[/tex]:
[tex]\[ (g - h)(-8) = g(-8) - h(-8) = 3 - (-1) = 3 + 1 = 4 \][/tex]
So, the value of [tex]\( (g - h)(-8) \)[/tex] is 4.
Therefore, the solution to the question is:
[tex]\[ (g-h)(-8) = 4 \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.